Antibiotic therapy adequacy to PROA flowchart in community-acquired pneumonia in moderate care patients (Actualizaciones en Sida e Infectología, 2025)
Introduction: Antimicrobial Stewardship Programs (ASP) use evidence-based flowcharts to standardize infection management. Their implementation is rarely evaluated, limiting the validation of their impact.Objective: To evaluate the adequacy of antibiotic treatment according to the ASP flowchart in patients with community-acquired pneumonia (CAP) hospitalized in a moderate care unit at a tertiary care center.Methods: Observational, retrospective study (April-December 2024) was conducted on 50 immunocompetent patients ≥18 years of age with CAP hospitalized in a moderate care unit. Six adequacy indicators were analyzed (empirical selection, dosage, time to first dose < 4 hours, therapeutic adjustment, sequential therapy, and treatment duration), classified as optimal (>90%), intermediate (60-90%), or low (
Keywords: Antimicrobial Stewardship; Community Acquired Pneumonia; Inpatients; Guideline Adherence